2017
DOI: 10.26480/gws.01.2017.07.09
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and identification of halophilic bacteria producing halotolerant protease

Abstract: Halotolerant proteases are known as one of the important groups of enzymes that have been used widely in various industries. However, high production cost of proteases in term of energy used for sterilization and high risk of microbial contamination during fermentation become the obstacles during upstream processing. Moreover, proteases that capable to withstand with harsh conditions of salinity, temperature and pH are required in industry. Therefore, this study presents newly isolated halophilic bacteria prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 12 publications
0
22
0
3
Order By: Relevance
“…The accelerated biofouling test showed that the bacteria can exhibit growth under conditions of very high salinity, in the range of 3%-8% salt concentration by weight (see Figure 8). This result suggests that the bacteria indeed exhibits sporulation, as endospore production allows the bacteria to survive in extreme environmental conditions [42,43]. In addition, the ability of Bacillus halotolerans MCC1 to biofoul RO membranes was also demonstrated in this test.…”
Section: Accelerated Biofouling Test On Ro Membranesmentioning
confidence: 54%
“…The accelerated biofouling test showed that the bacteria can exhibit growth under conditions of very high salinity, in the range of 3%-8% salt concentration by weight (see Figure 8). This result suggests that the bacteria indeed exhibits sporulation, as endospore production allows the bacteria to survive in extreme environmental conditions [42,43]. In addition, the ability of Bacillus halotolerans MCC1 to biofoul RO membranes was also demonstrated in this test.…”
Section: Accelerated Biofouling Test On Ro Membranesmentioning
confidence: 54%
“…This seaweed's body is yellowish-brown in color, is succulent and is rich in nutrition. Besides, it is rich in polysaccharides, proteins, and microelements which are beneficial to human body (Ma et al 2004;Xie et al 2014;Samad et al 2017). Due to the promising medical and food therapeutic effects, S. fusiforme have attracted a great deal of attention from both pharmaceutical and food industries.…”
Section: Mitogenome Announcementmentioning
confidence: 99%
“…Sedangkan Wardani dan Nindita (2012) berhasil mendapatkan 30 bakteri proteolitik dengan aktivitas protease yang beragam. Oleh karena itu, substrat yang digunakan sebagai sampel dalam mengisolasi bakteri proteolitik dapat diperoleh dari berbagai tempat yang banyak mengandung protein seperti limbah cair tahu, rumah pemotongan hewan, tambak, dan tempat pembuangan susu rusak serta tanah gambut yang kaya akan bahan organik, pada produk fermentasi terutama yang berbahan dasar kedelai seperti oncom (Lestari et al 2018) dan produk fermentasi ikan (Samad et al 2017). Isolasi dilakukan dengan menggunakan medium yang mengandung kasein, Zona bening yang merupakan substrat yang baik untuk mengisolasi bakteri penghasil enzim protease dan menginduksi sintesis enzim protease alkalin (Ward, 1983).…”
Section: Hasil Penelitian Dan Pembahasanunclassified